Treatment of palm oil mill effluent by electrocoagulation process - Mohd Nasrullah, Zulkifli (2017)
Palm oil mill effluent (POME) is known to be one of the major attributer to water pollution in Malaysia due to its high concentration of chemical oxygen demand (COD), biochemical oxygen demand (BOD) and suspended solid (SS). Various techniques of effluent treatment such as chemical coagulation, adsorption, filtration, aerobic and anaerobic treatment, ponding system etc., have disadvantages such as high retention time and substantive chemical substances. Therefore, in this study electrocoagulation technique was introduced and applied. This process offers some distinctive advantages including a simple set-up, effectively remove high concentration of pollutant, short treatment time and requires only a small treatment space. Electrochemical cell has been successfully designed for POME treatment by choosing the vertical over horizontal orientation which subsequently resulted the highest removal of 57, 53 and 5% for COD, BOD and SS respectively. Monopolar series (MP-S) has been chosen instead of monopolar parallel (MP-P) and bipolar (BP) as the electrode arrangement due to the highest removal of 65, 62 and 60% for COD, BOD and SS respectively. Steel wool has been chosen rather than iron and aluminium plate for the highest removal of 74, 70 and 66% of COD, BOD and SS respectively. Operating parameters such as electrolysis time, current intensity, inter-electrode distance and initial pH have a great influence on the removal of COD, BOD and SS. The best effective range of operating parameters to treat POME were found to be 30 to 50 minutes for electrolysis time, 15 to 20 A for current intensity, 5 to 15 mm for inter-electrode distances and 3 to 6 for initial pH value. Electricity consumption is often become the limiting factor in the electrocoagulation process, therefore in this research, the high intensity of the current (15, 20 and 25) has been introduced and studied to improve the effectiveness of the process. For particle size analysis, the average flocs size at first steady-state, floc size at breakage state, average size at second steady-state, strength factor, recovery factor, first growth rate and second growth rate were found to be 336 μm, 223 μm, 333 μm, 66.37%, 97.35%, 20.94 μm/min and 11.89 μm/min. The average flocs size at the second steady-state for 1, 5 10, 15 20 and 25 A of current intensity were 168, 252, 333, 463, 538 and 550 μm respectively. The average flocs size at the second steady-state for 5, 10, 15, 20, 25 and 30 mm of inter-electrode distances were 214, 228, 208, 168, 138 and 97 μm respectively. The average flocs size at second-steady state for pH 2, 3, 4, 5, 6, 7, 8 and 9 were found to be 216, 244, 275, 267, 236, 191, 175 and 163 μm respectively. The optimization study using response surface methodology (RSM) indicated that the optimal COD, BOD and SS removals were achieved at 19.07 A of current intensity, 44.97 minutes of treatment time, 8.60 mm of electrode distance and 4.37 of pH. The predicted results under this optimized condition were 97.21, 99.26 and 99.00% for COD, BOD and SS removal respectively. The validation experiment showed 95.03, 94.52 and 96.12% for COD, BOD and SS removal with 2.29%, 5.01% and 1.96% of standard error respectively. Overall, the treatment by using electrocoagulation process demonstrated an effectiveness and time saving technique for pollutant removal from POME.